Pengaruh Lingkungan Kerja dan Penguasaan Teknologi terhadap Kinerja Karyawan dengan Stres Kerja sebagai Variabel Intervening pada PT. Abaisiat Raya - Ohca Marcita; Fitri Yeni; M Afuan (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2025)
The purpose of this research is to examine the relationship between PT. Abaisiat Raya employees' performance, their work environment, and their level of technological proficiency, with the mediating effect of stress in the workplace. We use SEM Analysis with Partial Least Square (PLS) as our methodology. Through the distribution of surveys to sixty-eight participants. Here are some key findings from the study: At PT. Abaisiat Raya, we could not find any evidence that a favorable work environment reduced stress. At PT. Abaisiat Raya, one's level of technological proficiency correlates positively and significantly with their level of stress on the job. At PT. Abaisiat Raya, the relationship between the workplace and productivity is good and statistically significant. Performance at PT. Abaisiat Raya is negatively and significantly impacted by employees' level of technology mastery. Work stress has a favorable and statistically significant effect on PT. Abaisiat Raya employees' performance. As an intervening variable, work stress has a favorable but negligible effect on employee performance at PT. Abaisiat Raya. Technology Mastery and Employee Performance at PT. Great Abaissat are positively and significantly impacted by work stress as an intervening variable.